Basic provisions and problems of ELW technology for the manufacture of aluminum-magnesium alloys constructions - E. I. Pryakhin; N. I. Sharonov (Записки Горного института, 2018)
Existing problems of electron beam welding of aluminum alloy constructions are considered. For research purposes, the aluminum-magnesium alloy of grade 1561 up to 60 mm thick was used.